Study Of Cardiovascular Activities Of Gynura Procumbens Merr. Extract And Its Fractions - Kaur, Navneet (2013)
Gynura procumbens Merr. is an evergreen herb traditionally used for treatment of eruptive fevers, rash, kidney disease, diabetes and hypertension. In the present study, the cardiovascular effects-guided extraction and fractionation of G. procumbens was performed in an attempt to find the active extract and fraction. The plant was dried, milled and extracted with different concentrations of ethanol:water (95%, 75%, 50%, 25% v/v) and water. The extracts were dried under reduced pressure and later freeze-dried. The effect of the extracts was examined on isolated rat aortic ring and isolated right & left atrium. The water extract (GPWE) was found to be the most potent in relaxing phenylephrine (PE) precontracted aortic rings; isoprenaline (IsoP) induced maximum contractions and beats per minute for left & right atrium. By means of solvent-solvent extraction, the aqueous GPWE solution was fractionated using n-butanol. The effects of the freeze-dried fractions were then investigated in vitro on isolated aortic rings and atrium preparations. Among the two fractions, none retained the cardiovascular activity. Removal of the endothelium of the aortic ring completely abolished the vascular relaxing properties of GPWE also. The water extract (GPWE) also was found to be potent in lowering blood pressure and heart rate of anesthetized rats but alike ‘in vitro’ studies; the fractions of GPWE were less effective in lowering blood pressure and heart rate of anaesthetized rats.